2020
DOI: 10.3390/microorganisms8122017
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica in Invasive Lizard from Fernando de Noronha Archipelago: Serotyping, Antimicrobial Resistance and Molecular Epidemiology

Abstract: Salmonella infection can pose serious health issues, especially to children, elders or immunosuppressed humans. Wild populations of reptiles can reach Salmonella prevalence of up to 100% and the direct or indirect transmission from reptiles to humans have been extensively reported. Fernando de Noronha (FN) is an inhabited oceanic archipelago in the northeast coast of Brazil, with an economy based on tourism. The tegu (Salvator merianae) is the largest lizard native to South America and was introduced to the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(44 reference statements)
0
5
1
Order By: Relevance
“…In contrast to our results, Abrahão et al [37] have reported 13.3% of isolates from lizard resistant to colistin in Brazil. Given this growing evidence for antibiotic resistance, the importance of reptile-associated Salmonella spp.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Abrahão et al [37] have reported 13.3% of isolates from lizard resistant to colistin in Brazil. Given this growing evidence for antibiotic resistance, the importance of reptile-associated Salmonella spp.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher (76.9%) prevalences of Salmonella spp. were recorded in pet snakes, lizards, and tortoises from Poland [5], 64.5% in snakes and lizards from Norwegian zoos [1], and 32.6% in domestic snakes, chameleons, and lizards from central Europe [35], 43.28% of the pet reptiles carried from Western Romania [36], and 50.0% of the lizard from Fernando de Noronha Archipelago (Brazil) [37]. Te current study is one of the few studies to isolate Salmonella serovars from wild reptiles.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, after examination of faeces from 426 reptiles (322 anoles, 69 iguanas and 35 geckos) caught in Guadeloupe National Park, the frequency of S. enterica carriage was 15% (64/426, 15%) [59%]. In Slovenia, Romero et al [72] examined the presence of [73] China [74], Malaysia [75], Brazil [76,77], the US [52,78] Australia [79,80], New Zealand [81], Grenada [82], Canada [83] and Japan [12,64,84]. Relatively low Salmonella-prevalence was reported in 2020 in Japan.…”
Section: Salmonella Spp Prevalence In Amphibians and Reptilesmentioning
confidence: 99%
“…Taking into account non-European countries and the period 2015–2021, Salmonella -prevalence in reptiles was reported in Costa Rica [ 73 ] China [ 74 ], Malaysia [ 75 ], Brazil [ 76 , 77 ], the US [ 52 , 78 ] Australia [ 79 , 80 ], New Zealand [ 81 ], Grenada [ 82 ], Canada [ 83 ] and Japan [ 12 , 64 , 84 ]. Relatively low Salmonella -prevalence was reported in 2020 in Japan.…”
Section: Salmonella Spp Prevalence In Amphibians and Reptilesmentioning
confidence: 99%
See 1 more Smart Citation